2015
DOI: 10.1002/pmic.201500278
|View full text |Cite
|
Sign up to set email alerts
|

Improving genome annotation of enterotoxigenic Escherichia coli TW10598 by a label‐free quantitative MS/MS approach

Abstract: The most commonly used genome annotation processes are to a great extent based on computational methods. However, those can only predict genes that have been described earlier or that have sequence signatures indicative of a gene function. Here, we report a synonymous proteogenomic approach for experimentally improving microbial genome annotation based on label-free quantitative MS/MS. The approach is exemplified by analysis of cell extracts from in vitro cultured enterotoxigenic Escherichia coli (ETEC) strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Abundance differences were log 2 -transformed and visualized with boxplots ( Figure 2 B ). As highlighted in Figure 2 C , the log-transformed LFQ values display a prototypical profile [32] .
Figure 2 Overview of proteomic results.
…”
Section: Resultsmentioning
confidence: 93%
“…Abundance differences were log 2 -transformed and visualized with boxplots ( Figure 2 B ). As highlighted in Figure 2 C , the log-transformed LFQ values display a prototypical profile [32] .
Figure 2 Overview of proteomic results.
…”
Section: Resultsmentioning
confidence: 93%
“…Use was made of the Biopython software package 5 (Cock et al, 2009 ). Pettersen et al ( 2015 ) only considered proteins identified in at least two replicates in their proteogenomic analysis of enterotoxigenic Escherichia coli —similarly, we only considered peptides identified in at least two replicates for further analysis. All peptides were searched against the genome dynamically translated in the six reading frames, and peptides unique to a single position in the genome were identified.…”
Section: Methodsmentioning
confidence: 99%
“…11 Sequence gap-closing was performed as previously described for TW10598 including checking the assembly against optical maps of each strain's chromosome. 25 Here, we also resequenced the genome of each strain on an Illumina HiSeq 2000 machine by using Illumina HiSeq v4 reagents on 300 bp libraries and aligning the resulting 125 bp paired-end reads against the completed assemblies to further identify and correct any mis-assemblies. Not all plasmid sequences could be completely assembled due to long stretches of repeat elements among the plasmid sequences.…”
Section: Genome Assembly and Annotationmentioning
confidence: 99%